Modeling early Epstein-Barr virus infection in Drosophila melanogaster: the BZLF1 protein. - Adamson, A.L.; Wright, N.; LaJeunesse, D.R. (Genetics, 2005)
Epstein-Barr virus (EBV) is the causative agent of infectious mononucleosis and is associated with several forms of cancer, including lymphomas and nasopharyngeal carcinoma. The EBV immediate-early protein BZLF1 functions as a transcriptional activator of EBV early gene expression and is essential for the viral transition between latent and lytic replication. In addition to its role in the EBV life cycle, BZLF1 (Z) also has profound effects upon the host cellular environment, including disruption of cell cycle regulation, signal transduction pathways, and transcription. In an effort to understand the nature of Z interactions with the host cellular environment, we have developed a Drosophila model of early EBV infection, where we have expressed Z in the Drosophila eye. Using this system, we have identified a highly conserved interaction between the Epstein-Barr virus Z protein and shaven, a Drosophila homolog of the human Pax2/5/8 family of genes. Pax5 is a well-characterized human gene involved with B-cell development. The B-cell-specific Pax5 also promotes the transcription of EBV latent genes from the EBV Wp promoter. Our work clearly demonstrates that the Drosophila system is an appropriate and powerful tool for identifying the underlying genetic networks involved in human infectious disease.